Kepastian Hukum Redistribusi Tanah Objek Reforma Agraria (Tora) Hasil Penataan Aset Kepada Masyarakat dalam Rangka Pelaksanaan Reforma Agraria - Nanda Aprilia Nurcahyaningrum; Ida Nurlinda; Betty Rubiati (As-Syar i: Jurnal Bimbingan & Konseling Keluarga, 2025)
Agrarian reform is a strategic policy to create equitable distribution of land tenure and people's welfare. Land Redistribution Object Agrarian Reform (TORA) is the main instrument to overcome inequality in land tenure. This policy aims to provide legal certainty for land recipient communities and encourage productive and sustainable land use. However, in its implementation, there are still various obstacles, such as land disputes, uncertainty about the status of land laws, and a lack of policy synergy between the central and regional governments. Based on this description, the purpose of this study is to examine the implementation of asset structuring through TORA redistribution in providing legal certainty for Agrarian Reform subjects and to find out the legal protection of ownership for Agrarian Reform subjects whose land objects are problematic as reviewed from Presidential Regulation Number 86 of 2018 or Presidential Regulation Number 62 of 2023. The research method used is normative juridical with a legal approach and case studies located in Ngargosari village, Kendal Regency and Pagerwangi Punclut village, West Bandung Regency. The data collection technique was carried out through literature studies and interviews with the local Land Office. The data analysis method uses qualitative normative analysis. The results of the study show that legal certainty on TORA redistribution in Indonesia already exists. However, in its implementation, there are still several obstacles, especially in the lack of transparency in the redistribution process and the lack of supervision over the implementation of the TORA redistribution policy. In addition, legal protection for the subject of Agrarian Reform is still not optimal. Therefore, concrete steps are needed to ensure that the land objects distributed are free from disputes, the priority resolution of land conflicts, and the improvement of legal assistance and inter-institutional coordination to ensure legal certainty and protection for the subject of Agrarian Reform.